Pesan Kemanusiaan Dalam Medium Sinema: Film Hollywood Sebagai Media Penyebaran Nilai-nilai Hak Asasi Manusia Universal - Syahputra, Eqqi; Rosyidin, Mohamad; Hanura, Marten (Journal of International Relations, 2021)
Hollywood has become the mainstream of globalization and the standard for cinema in various parts of the world. Not infrequently, Hollywood films can also convey messages about human life problems, including in terms of human rights. On the basis of fighting for and spreading human rights values, many films in the Hollywood film industry have started to act as a medium to spread human rights values into their film productions. Thus, this paper aims to answer and further examine how the roles of Hollywood films they give to the delivery of messages of universal human rights values. The scope of this research will focus on the value of human rights, films in the politics of international relations, as well as Hollywood films that have story content that adheres to human rights values and messages. The author will collect data using the literature study method with data sources referring to films, journals, books, websites, and international news. The data analysis technique will use Discourse Analysis because of its suitability with the theory, in this case post-structuralism, and to reveal every message in each film sample. This research allegation shows that some filmmakers, through their films which are thick with language and representation, can become media to disseminate values and understandings about human rights that they want to spread, and have a direct impact on the wider community.